Public Debts Trends in the Current Economic Context, from Both National and International Perspective - Dascalu, Doina; Ungureanu, Dragos (Journal of Economic Development, Environment and People, 2015)
. The article presents an analysis of the way public debt operates in Romania, in the context of states economies trends, of complex and topical financial environments. In the context of a functional market economy, the issues faced by certain states involving high public debt levels or potential budgetary pressure risks converge towards the idea that public finances sustainability needs to be a major challenge at the level of public policies. Considering this situation, the adequate policies to tackle public finances sustainability need to have, as a launching base, the overall strategy of the European Union, focused on the three component parts, namely abatement of public debt, increasing productivity and employment and last but not least, reforming the pension and healthcare systems. To ensure reasonably sustainable public debt levels, EU member states need to attain medium term strategic budgetary objectives, that would ensure a downward trend of public debt, a condition which can be fulfilled by compliance with budget policies rules, which ground development in the macroeconomic framework.